Negative Pressure Treatment for Abdominal Wall Pseudotumor Due to Fishbone Perforation - Livideanu C; Alassiri A; Paolino L; Martini F; Droz J; Fritsch S (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2016)
The inadvertent swallowing of foreign bodies is common, but results in perforation of the gastrointestinal tract in less than 1% of cases [1]. Because any site of the gastrointestinal tract may be perforated by a foreign body, the clinical presentation may vary and mimic diverse medical conditions.  Presentation may be early in the form of peritonitis or late in the form of intra-abdominal abscess. Up to date no case of abdominal wall abscess was reported. Herein we describe the clinical history of a 60 year-old man presenting with an abdominal wall pseudo tumor due to accidental fishbone ingestion occurred 8 months before. After surgical drainage of the abscess, negative pressure wound therapy (NPWT) was used with excellent results.